The Impact of Climate and Weather on a Small Tourism Business: A wSWOT Case Study. (July 2019) - Craig, Christopher A.; Sayers, Elizabeth Petrun; Feng, Song; Kinghorn, Brent
Climatic variability and shifting weather patterns, resulting in extreme weather events and natural disasters, pose risks to small businesses in the United States. This is particularly true in coastal regions of the southeast United States where extreme events such as hurricanes, flooding, and thunderstorms are projected to increase in frequency and intensity. Yet, the vast majority of small business owners do not have a disaster plan in place and an estimated 40% to 60% of small businesses that have experienced a natural disaster never reopen. This teaching case explores the impact of climatic trends and weather on one location of an outdoor tourism industry business in the coastal community of Virginia Beach, Virginia. The case draws from observed weather and sales data for the local small business. Students will draw from descriptive statistics, statistical analysis, and graphs to explore (a) long-term climatic trends for the business; (b) relationships between small business sales and local weather; and (c) strengths, weaknesses, opportunities, and threats relative to weather conditions and climate change. Instructors can give the body of this document to students. They can also make use of the supplemental teaching notes to assist them with teaching this case.